Long-legged bees make adaptive leaps: linking adaptation to coevolution in a plant–pollinator network. Issue 1862 (13th September 2017) - Pauw, Anton; Kahnt, Belinda; Kuhlmann, Michael; Michez, Denis; Montgomery, Graham A.; Murray, Elizabeth; Danforth, Bryan N.
Abstract : Adaptation is evolution in response to natural selection. Hence, an adaptation is expected to originate simultaneously with the acquisition of a particular selective environment. Here we test whether long legs evolve in oil-collecting Rediviva bees when they come under selection by long-spurred, oil-secreting flowers. To quantify the selective environment, we drew a large network of the interactions between Rediviva species and oil-secreting plant species. The selective environment of each bee species was summarized as the average spur length of the interacting plant species weighted by interaction frequency. Using phylogenetically independent contrasts, we calculated divergence in selective environment and evolutionary divergence in leg length between sister species (and sister clades) of Rediviva . We found that change in the selective environment explained 80% of evolutionary change in leg length, with change in body size contributing an additional 6% of uniquely explained variance. The result is one of four proposed steps in testing for plant–pollinator coevolution.